Effects of intraruminal infusions of sodium salts on selection of hay and concentrate foods by sheep - Engku Ahmed, Engku Azahan; Forbes, J. M. (Elsevier Ltd., 2005)
Infusion of salts of short-chain fatty acids into the rumen of sheep depresses food intake but the relative importance of the effect of the acids and of osmolality are not fully understood. Three experiments were carried out in which sodium acetate (NaAc) and sodium chloride (NaCl) were infused for 3 h at 4 m /min and compared with water controls. The effects on the intakes of a concentrate food and hay were examined to study the effect of osmotic and acid manipulation of the rumen on dietary choice. In the first experiment the foods were continuously available while in the second and third the foods were given for 3 min at 1.5-h intervals.